Analysis of Fraud Committed Through Information Technologies - Uralov Sarbon Sardorovich (International Journal of Law And Criminology, 2025)
This article discusses the most common types of fraud committed in the era of modern information technologies. Basically, in the modern world, cases such as illegally acquiring someone else's property under the guise of social relations, giving it a legal appearance, or staging the method of committing a fraud crime as if it were civil legal relations are covered from a scientific and practical point of view. The conclusion reflects proposals and recommendations aimed at being aware of this crime and preventing becoming its victim.